2013
DOI: 10.1111/jgs.12144
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Functional Decline in Hospice: What Can Individuals and Their Families Expect?

Abstract: Objectives To describe the trajectory of patients’ functional decline after they are referred to hospice. Design Electronic health record-based retrospective cohort study. Setting Three hospice programs in the southeast, northeast and Midwest US. Participants Hospice patients. Main outcome measures Palliative Performance Scale (PPS) scores measured at intervals between hospice enrollment and death, on a scale from 10–100. Results Of 8,669 decedents, there was an average 13.8-point decline in PPS scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…Specific diseases are associated with certain patterns of decline, 11-13 but we find that diseases are not associated with particular spending trajectories. Instead, it is the number of conditions that appear to be most relevant to end-of-life spending.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Specific diseases are associated with certain patterns of decline, 11-13 but we find that diseases are not associated with particular spending trajectories. Instead, it is the number of conditions that appear to be most relevant to end-of-life spending.…”
Section: Discussioncontrasting
confidence: 68%
“…Prior work has suggested that certain diseases are associated with a pattern of decline that may be reflected in spending. 11-13 More detailed information about the course of spending near the end-of-life may provide important insights about the drivers of end-of-life spending and shed light on potential strategies to mitigate the costs while preserving high quality care for people who are dying. 14 …”
mentioning
confidence: 99%
“…1,2,13,14,24 These prospectively collected data mirror some longer prospective 2,24 and retrospective 1,25 trajectory studies for cancer, organ failure, 2,13,14 and frailty/dementia. 2,12,14 Data show there are rapid periods of decline in the last 14 -22 days of life for all diagnostic cohorts, with the average AKPS score dropping by 15 -26 points.…”
Section: Significance Of the Findingsmentioning
confidence: 99%
“…16 Consequently, many older persons do not receive hospice or palliative care near the end of life, 17,18 which can place a high burden on caregivers 19 and result in suffering. 20 Although functional decline among patients in hospice has been previously evaluated, 21,22 the course of disability before hospice has not been well characterized. Several prior studies [23][24][25][26] have evaluated the prevalence and time course (or trajectory) of disability at the end of life, but have not focused on the functional antecedents to hospice admission.…”
Section: Introductionmentioning
confidence: 99%